Egg Allergy in infancy - Shrestha, R; Shrestha, D; Poudyal, R; Mishra, N (Nepal Journal of Dermatology, Venereology & Leprology, 2012)
Egg allergies are one of the most common allergies of childhood and the reactions may vary from mild to severe. A family history of egg allergy or atopy is a risk factor for egg allergy. Most food-induced allergic reactions occur on first known oral exposure, especially in the case of eggs and peanuts. We report a case of nine months old infant who developed egg allery (contact dermatitis) after contact with egg white, with a positive family history of atopy and egg allergy. Keywords Egg allergy; contact dermatitis; infancy. DOI: http://dx.doi.org/10.3126/njdvl.v9i1.5766 NJDVL 2010; 9(1): 28-30